Effectiveness Of Advertisement: Traditional Vs. New Media - Saxena, Chandan (The journal of contemporary issues in business and government, 2021)
In the era of digitalization everything is just a click away. The revolutionary concept of globalization has made every information easily accessible. It is a platform that provides a vast knowledge of every product in few seconds. The trend of digital marketing and social media marketing has replaced the traditional marketing methods as well as advertisements methods. The traditional methods of advertising, which are most credible and authentic are turning old fashion in front of social media advertising. Since, social media advertising are more convenient, easy to access and affordable, the shift has endangered the survival of traditional methods. The methodology used is to study the impact of social media advertising on traditional methods of advertising and how people are moving towards modern advertising tools. This is a descriptive analysis to understand the connectivity between the media and the users. The results demonstrate that sharing of advertisements on Social Media increases its exposure as well as its attractiveness but it is still not as trustworthy as the traditional media platforms. To accomplish this research the researcher will use survey method in which the sample of 100 participants from media department of Chandigarh University will be taken into consideration.